Distinct Microbiomes of Gut and Saliva in Patients With Systemic Lupus Erythematous and Clinical Associations - Liu, Fengping; Ren, Tianli; Li, Xiaodi; Zhai, Qixiao; Xu, Xifeng; Zhang, Nan; Jiang, Peng; Niu, Yaofang; Lv, Longxian; Shi, GuoXun; Feng, Ninghan (Frontiers in Immunology, 2021)
Alterations in the microbiome of the gut and oral cavity are involved in the etiopathogenesis of systemic lupus erythematosus (SLE). Bladder microbiome is responsible for the health status. We aimed to assess whether all microbiome compositions in urine, feces, and saliva were specific in patients with SLE. A total of 35 patients with SLE, as well as sex- and age-matched healthy controls (HC) were recruited. Catheterized urine, fecal swabs, and saliva samples were collected from the participants. 16S ribosomal RNA gene sequencing was performed on the samples. Compared with the HC group, reduced bacterial richness and increased diversity were detected in the urine of patients with SLE, along with decreased bacterial richness and diversity in their feces, and increased bacterial diversity in their saliva. Urine samples better explained the cohort variation than feces and saliva samples. In urine, a bacterium in the Enterobacteriaceae family was predominant and related to disease duration and activity. Pseudomonas responded positively to the levels of serum C3 and C4. The feces were characterized by enrichment of Lactobacillus, and depletion of an unclassified bacterium in the Ruminococcaceae family and Bifidobacterium. Lack of Bifidobacterium was observed in patients with arthritis. Akkermansia and Ruminococcus negatively correlated with the serum levels of C3. In saliva, Veillonella, Streptococcus, and Prevotella were dominant, and Bacteroides was negatively associated with disease activity. These findings can assist us to comprehensively understand the bacterial profiles of different body niches in SLE patients.